Peace Education for Justice: Sowing Human Rights Awareness - Andi Akbar Wury (CV. Publikasi Indonesia, 2024)
This research aims to examine in depth the role of peace education in the context of Human Rights (HAM) and social justice, as well as how its implementation can strengthen human rights understanding and promote social justice in the midst of the complexity of today's global challenges. This research uses a qualitative approach with a focus on literature studies to identify the role of peace education in strengthening human rights understanding and promoting social justice. The results of the study show that peace education not only serves as an instrument to teach human rights theory, but also to change the attitudes and behaviors of individuals and society as a whole. The implications of this research include the importance of integrating peace values in educational curricula, training for educators, and building partnerships with civil society to create more peaceful, just, and inclusive societies.